Przykłady Obliczenia Krzywych Nośności Granicznej - Wnuk, M. (Engineering Transactions, 1963)
This paper is devoted to effective determination of the limit load of bars of various forms of the cross-section often met with in engineering practice. In particular are treated profiles having the form of a regular triangle, square, hexagon, any regular polygon, circle, ellipse, circular ring circle with a circular hole, square with central circular hole (drills for oil pits) thin walled structures with constant wall thickness (closed, such as box beams, and open).